2015
DOI: 10.1038/pcan.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative low serum testosterone is associated with high-grade prostate cancer and an increased Gleason score upgrading

Abstract: Low serum testosterone is an independent risk factor for predominant Gleason pattern 4 on prostate specimen after RP and for upgrading from low- to high-grade cancer between prostate needle biopsies and RP specimen. This observation should be taken into account in localised PCa management, especially for active surveillance or when a nerve-sparing approach is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
2
24
0
2
Order By: Relevance
“…Pichon et al [33] had shown in a larger study population that a low serum testosterone level was an independent predictor of a predominant Gleason pattern 4 at radical prostatectomy and of upgrading from low- to high-grade PCa between needle biopsies and prostatectomy specimens. Accordingly, the San Francisco et al study [31] showed that men on AS with low serum free testosterone levels had more than four times the risk of disease reclassification, suggesting the need for further studies to assess testosterone as a tool to better select patients for AS.…”
Section: Discussionmentioning
confidence: 99%
“…Pichon et al [33] had shown in a larger study population that a low serum testosterone level was an independent predictor of a predominant Gleason pattern 4 at radical prostatectomy and of upgrading from low- to high-grade PCa between needle biopsies and prostatectomy specimens. Accordingly, the San Francisco et al study [31] showed that men on AS with low serum free testosterone levels had more than four times the risk of disease reclassification, suggesting the need for further studies to assess testosterone as a tool to better select patients for AS.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors from the literature include low prostate volume/weight, 3 higher PSA level,5, 22, 23 higher PSA density, 24 older age, 5 clinical stage T2, 25 time interval between diagnosis to RP,7, 23 percentage positive biopsy cores,7, 22 Cancer of the Prostate Risk Assessment (CAPRA) score, 22 higher body mass index,22, 24 and low serum testosterone 8 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined variables that may help to predict pathological upgrading of GS from biopsy to RP, including high prostate-specific antigen (PSA) level, 5 advanced patient age, 5 the level of pathologist expertise, 6 time from biopsy to surgery, 7 serum testosterone level, 8 treatment with brachytherapy, 9 percentage tumor involvement, 10 prostate size or volume, 1 and number of core biopsies 11 …”
Section: Introductionmentioning
confidence: 99%
“…19 Similarly, Pichon et al showed, among subjects undergoing RP for PCa, that lower testosterone levels were associated with higher-grade PCa and with increased risk of GS upgrading from prostate biopsy to specimens from surgery. 20 Park et al 9 demonstrated a correlation between hypogonadism and unfavorable outcomes in prostatic biopsies, such as increased incidence of GS ≥ 8. Several studies, despite adopting different thresholds for the definition of hypogonadism, have confirmed an association between low testosterone levels and adverse characteristics and outcomes for PCa, including higher Gleason score, 21,22 higher pathological stage 10,22 and increased risk for disease progression.…”
Section: Discussionmentioning
confidence: 99%